PbI2 platelets for inverted planar organolead Halide Perovskite solar cells via ultrasonic spray deposition. (15th June 2017) - Chai, Gaoda; Wang, Shizhen; Xia, Zhonggao; Luo, Shiqiang; Teng, Chao; Yang, Tingbin; Nie, Zanxiang; Meng, Tiejun; Zhou, Hang
Abstract: Morphology control of organometal halide perovskite thin films is of importance in order to develop highly efficient perovskite solar cells. Here, a seeded growth method is introduced for the first time to deposit lead iodide (PbI2 ) with platelet structures on an organic hole transporting layer PEDOT:PSS. The PbI2 platelets are effectively converted into perovskite thin film when subject to sprayed droplets of methylammonium in isopropyl alcohol. Compared with evaporated compact PbI2 layers, the PbI2 platelet enables a thicker perovskite thin film to be formed with less unreacted PbI2 . Using this technique, we have achieved pinhole-free and uniform perovskite thin film with root-mean-square roughness of 12.81 nm, and an average solar cell efficiency higher than those fabricated from compact PbI2 thin film.